Intracerebroventricular Injection of L-Pipecolic Acid Exerts Hypnotic Effects Without Activating NMDA Receptors in Neonatal Chicks under Social Isolation-induced Stress - Asako Shigemura; Vishwajit S. Chowdhury; Mitsuhiro Furuse (The Journal of Poultry Science, 2020)
L-Pipecolic acid is an intermediate of L-lysine catabolism. Its central injection exerted a hypnotic effect on the brain, which was partially mediated by the activation of γ-aminobutyric acid-A and γ-aminobutyric acid-B receptors. L-Proline has also been shown to exert a similar effect on N-methyl-D-aspartate receptors. Furthermore, L-pipecolic acid is known as L-homoproline, and both L-pipecolic acid and L-proline belong to the imino acid group; therefore, it is plausible that they share certain commonalities, including similar functions. However, the role of N-methyl-D-aspartate receptors with respect to the effects of L-pipecolic acid has not been examined yet. In the present study, the relationship between N-methyl-D-aspartate receptors and the central function of L-pipecolic acid was investigated in neonatal chicks. The behavioral postures for active wakefulness and standing/sitting motionless with eyes opened were significantly affected after intracerebroventricular injection of L-pipecolic acid; whereas, sitting motionless with head drooped (sleeping posture) was significantly enhanced. However, the N-methyl-D-aspartate receptor antagonist, MK-801, did not affect these changes. In conclusion, the central administration of L-pipecolic acid did not exert hypnotic effects through the activation of N-methyl-D-aspartate receptors in neonatal chicks. These results suggest that the imino group is not a determinant for activating N-methyl-D-aspartate receptors.